How Significant is Partnership Formation in Area-Based Projects to Increase Parental Attendance at Maternal and Child Health Services? - Kelaher, Margaret; Dunt, David; Nolan, Andrea; Raban, Bridie; Walker, Rae (International Journal of Child Health and Nutrition, 2013)
Objectives: In this study, we assess the importance of area-based partnerships in an initiative to improve access to Maternal and Child Health (MCH) services (known as Best Start) in socially disadvantaged communities in Victoria, Australia. Methods: The study assessed changes in MCH attendance rates, parental attitudes and local partnership formation before and after the introduction of Best Start projects. Partners involved in Best Start projects were surveyed regarding the extent of local partnership formation (before 54; after 84). Data was collected for MCH attendance using routine records for Best Start with MCH projects (before 1,739; after 1437) and the rest of the State (before 45,497; after 45,953). Two cross-sectional surveys of parents of 3-year old children were used to assess changes in parent’s knowledge about, and confidence in using relevant services as well as parental confidence more generally (before 1666; after 1838). Results: Best Start was significantly associated with improving: levels of partnership formation (5 of 7 relevant factors) attendance at the 3.5 year MCH visit in Best Start Sites with MCH projects between 2001/02-2004/05. parent’s access to information (partnership effect); confidence about attending the 3.5 year MCH visits (partnership effect); and overall parental confidence (project effect only). Conclusion: Best Start improves participation in the MCH attendance. This is related most directly to improving parent’s access to information and overall parental confidence either through local partnership or direct project effects.